Basis of resistance in wheat genotypes to Bipolaris sorokiniana causing spot blotch disease - B.M. BASHYAL, J. KUMAR and M. JINDAL, V. PRASANNA KUMAR*, R. AGGARWAL, S. BANERJEE, S. GUPTA, S. SHARMA, (Indian Phytopathology, 2013)
Bipolaris sorokiniana is a hemibiotrophic pathogenic fungus causing spot blotch of wheat. We investigated the interaction of differentially behaving wheat genotypes against this pathogen. Seven wheat genotypes were evaluated for resistance under artificial inoculation (AI) at seedling stage; and natural and AI conditions at adult plant stage at Delhi, Ludhiana and Wellington, Tamil Nadu. Of the entries screened, none of the genotypes showed immunity to the disease, whereas Chiriya 3, Chiriya 7 and Chiriya 1 showed resistance both at seedling and adult plant stage when tested at different locations. Two genotypes viz., Milan/Shanghai 7 and Shanghai 4 were moderately resistant where as HD2932 and Sonalika were moderately susceptible and susceptible respectively under both field and polyhouse conditions. Trichomes per microscopic field were more in Chiriya 7 genotype than in Sonalika, whereas percent conidial germination was high on Sonalika with maximum appressoria formation.